A new species of the ant genus Recurvidris Bolton, 1992 (Hymenoptera, Formicidae, Myrmicinae) from Thailand - Jaitrong, Weeyawat (Zookeys, 2019)
Abstract. Recurvidris Bolton, 1992 is a small myrmicine genus of the tribe Crematogastrini. Until now, eleven species are known in this genus from Asia. A new species, Recurvidrislekakulisp. n., is here described from Thailand based on the worker caste. The type series of the new species was collected from leaf litter in a dry evergreen forest. A key to the Asian species of Recurvidris based on the worker caste is provided.